Kualitas Protein dan Komposisi Asam Amino Ampas Sagu Hasil Fermentasi Aspergillus niger dengan Penambahan Urea dan Zeolit - La Ode Muhsafaat; Heri Ahmad Sukria; . Suryahadi (Jurnal Ilmu Pertanian Indonesia, 2015)
This experiment was designed to evaluate protein quality and amino acid composition of fermented sago pulp by Aspergillus niger with urea and zeolit addition at different levels. The experiment was design in factorial completely randomized with two factors and three replicates. The first factor was levels of urea addition (0, 2.5, and 5%), the second factor was levels of zeolite addition (0, 2.5, and 5%) and used 2% A. niger on sago pulp (dry matter form). Variables observed were the levels of crude protein and amino acids. Data were tested using descriptive and Analysis of Variance (ANOVA), the differences among treatments means examined by Duncan Multiple Range Test. The results howed that there was interaction between levels of addition urea and zeolite on crude protein value. The addition urea and zeolite at 5% had the high increased 15.49 ± 0.33% to crude protein content. The amino acid content of fermented sago pulp descriptively increased in urea treatment, but didn’t show increased in zeolite treatment. Based on the calculation of the score of chemical and index essential amino acids, fermented sago pulp at 5% urea treatment has a chemical score of 17.86, 18.01, and 11.85 with the essential amino acid deficient is leucine, and has an index of 38.33, 36.43, and 28.45%.